RHINOCEROS SOFTWARE AS A DIGITAL MODELING DEVELOPMENT OF 3D PRODUCTS Case Study: Students’ Digital Model Design of Product Design Department Telkom University - Alvian Fajar Setiawan; Chris Chalik (Balong International Journal of Design, 2020)
ABSTRACT The current technological development is very fast, it requires designers to adapt to these conditions. So that the use of CAD (Computer Aided Design) software is absolutely essential for designers to master. One that is included in the CAD software is Rhinoceros, a computer graphics software that is used to simplify the work and development of 3D modeling. Rhinoceros is widely used by industries such as architecture, industrial product design, multimedia and graphic design. This research is a qualitative research with an art and design approach. This research raises a case study from the work of 3D product modeling designed by product design students to be used as data analysis material. The data analysis process is carried out through literature study, observation and interviews with sources in order to produce an understanding of how to design and develop the initial concept into good 3D modeling. Keywords: Rhinoceros, Design, 3D Design, Product Designers